National Assessment of Achievement of Students Completing Grade 08 in Year 2007 - National Education Research and Evaluation Centre, University of Colombo (University of Colombo, 2007)
National Assessment of Achievement of Students Completing Grade 08 in Year 2007 National Assessment of achievement of Grade 08 students in the year 2007 in Sri Lanka is a national level study carried out by the National Education Research and Evaluation Centre, Faculty of Education, University of Colombo. This study conducted on 5th July 2008 is aimed at assessing the achievement levels of students who have completed Grade 08 in the year 2007. The total number in the sample was 10882 from 364 schools. The same test papers used for measuring achievement levels in First Language, Science and Technology and Mathematics were utilized for this study too. Chapter one of the report outlines the international background of National assessments. Various steps taken by the Sri Lankan governments since 1940’s to the improvement of general education are discussed. The findings of the grade 08 study conducted in year 2005 are also summarized in this chapter. In the second chapter the objects of the former study, framework of the present study sample of students selected, achievements tests used, data collection process adopted, methods of data analysis, limitations of the study and the format of the research reports are discussed. The chapter three mainly concentrates on discussing the general patterns in performance in Grade 08 students in the three subjects tested. In chapter four attention is focused on how the provision of equal opportunity in education has happened in relation to various groups. Achievements of Grade 08 students by the various abilities in these subjects is discussed in chapter five. Chapter six highlights how the Grade 08 students have reached the level of mastery in the three subjects tested. Findings: On average there is an improvement in Science and Technology and Mathematics. No improve is seen in First Language achievement levels. In all the provinces there is an improvement in Mathematics achievement levels. There are large inequalities in the provision of education at junior secondary level for the various categories such as provinces, male female, urban rural and medium of instruction. Emphasis of the curriculum developers and teachers on developing various abilities of students in the subjects has been inadequate. This has resulted in low achievement levels of students in sub skills. The percentage of students reaching the levels of mastery seems to be inadequate. Suggestions: To overcome the shortcomings identified through this study, improvement in curriculum designing and implementation, reconsidering, revitalizing and evaluation in general education, introduction of diagnostic and remedial intervention programmes, introducing action research programme at school level and minimizing differences among schools are recommended.